Enabling Retention of Rural Youth in Farming through Capacity Building – A Case Study - B. L. Dhaka; K. Chayal (Indian Journal of Extension Education, 2014)
Youth contributes more than 40 per cent of Indina rural populatin. Due to their limited access to education and skills training, rural youth are often very low-skilled, unemployed and insecure. Youth living in rural areas do not have enough incentives, profitable economic opportunities and attractive environments in which to live and work. Investing in young people living in rural areas is key to enhancing agricultural productivity, boosting rural economies, and reducing rural-tourban migration. Realizing the potentiality of agriculture to significantly reduce poverty, enhance economic growth and entrench economic stability, the rural youth were equipped with necessary skills required to run dairy farm successfully through capacity building activities. The present paper is based on findings of a case study. A case study of a successful dairy entrepreneur in Bundi district of Rajasthan state was conducted to analyse the effectiveness of capacity building strategy to retain rural youth in farming. It was observed that capacity building approach enabled the rural youth to run dairy farm enterprise profitably. The study concluded that capacity building of rural youth could play an important role in retaining rural youth in farming.